Menelaah Konsep Tashgir Dalam Julukan Bangsa Arab - Narliyani, Lista Dwi (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
Tashghir is an important morphological process in Arabic that not only functions to diminish meaning, but also to convey nuances of insult, affection, and closeness. Arabs often use nicknames in the concept of tashghir. The findings of the study show that in this context, terms or nicknames are often used to refer to individuals in a softer or more affectionate way. Like the term Zuhair which means small flower/blooming flower, which symbolizes beauty and elegance. In this concept of tashghir, several important aspects can be found in Arabic, especially in the use of names and terms. By using a Sociolinguistic approach, this study provides an understanding of the social and cultural context of the use of tashghir. This study aims to examine the function of tashghir in the formation of Arab nicknames, in a social and cultural context. The approach used is qualitative with sociolinguistic analysis that includes morphology that can examine the use of tashghir in nicknames that reflect social relations, norms, and cultural values in Arab society, so that it can create closeness and intimacy between individuals.